2006
DOI: 10.1007/s00210-006-0109-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbenoxolone on syncytial electrical properties and junction potentials of guinea-pig vas deferens

Abstract: The effects of the putative gap junction blocker carbenoxolone on smooth muscle syncytial properties and junction potentials were studied in guinea pig vas deferens (GPVD). Treatment with 50 muM carbenoxolone reversibly and significantly increased input resistance (R (in)) (by 682.5 +/- 326.0 %, P < 0.05) and abolished cable potentials within 6-7 mins of incubation, without disturbing resting membrane potential. Carbenoxolone reversibly and significantly increased the amplitude of spontaneous excitatory juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…3). In previous studies, both palmitoleic acid and carbenoxolone were shown to inhibit gap junctional communication in a concentration-dependent manner without extra-junctional effects at the concentrations used in the present study [17,27,28,29]. The role of gap junctions for conducted vasomotor responses was originally proposed by Segal et al [2 ]and Segal and Duling [5] based on studies performed in hamster cheek pouch arterioles.…”
Section: Discussionmentioning
confidence: 81%
“…3). In previous studies, both palmitoleic acid and carbenoxolone were shown to inhibit gap junctional communication in a concentration-dependent manner without extra-junctional effects at the concentrations used in the present study [17,27,28,29]. The role of gap junctions for conducted vasomotor responses was originally proposed by Segal et al [2 ]and Segal and Duling [5] based on studies performed in hamster cheek pouch arterioles.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, our studies show that for syncytia of larger sizes, the input resistance of a cell is markedly affected following changes in intercellular coupling, while the effect is limited in smaller syncytia. Experimentally, measuring the input resistance before and after the application of agents that reportedly modulate gap junctional conductance, such as carbenoxolone (Palani et al 2006;De Groot et al 2003), 18β-glycyrrhetinc acid (18β-GA) (Hashitani et al 2001) and 2-aminoethoxydiphenylborate (2-APB) (Hashitani et al 2004), could furnish information regarding the size of the syncytium in which the recorded cell is located. Simultaneous electrical and optical recordings, such as those conducted for vas deferens (Young et al 2007), could be carried out to verify the correlations our model postulates between SEJP properties and syncytial size.…”
Section: Resultsmentioning
confidence: 99%
“…The immunohistochemical findings in the present work assume that the lack of Cx43-IR, in the donkey, may be compensated by the S100immunoreactive dense network of nerves both in the lamina propria and tunica muscularis. Occurrence of gap junctions (Cx-binding sites) might reveal the reciprocal relationships between the ductal epithelium and the periductal components, necessary for regu-lation of the different functions (Segretain and Falk, 2004;Palani et al, 2006;Hejmej et al, 2007) of the duct.…”
Section: Discussionmentioning
confidence: 99%